2000
DOI: 10.1086/312921
|View full text |Cite
|
Sign up to set email alerts
|

A New Look at Simple Inhomogeneous Chemical Evolution

Abstract: A rudimentary, one-zone, closed-box model for inhomogeneous chemical evolution is offered as an alternative reference model, distinct from the Simple Model, in the limit of no mixing. The metallicity distribution functions (MDFs) of Galactic halo and bulge stars can be matched by varying a single evolutionary parameter, nQ. Q is the filling factor of contaminating regions, and n is the number of star-forming generations. Therefore, Q and n have equivalent roles, and combinations of n and Q yield systems with d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(94 citation statements)
references
References 13 publications
2
90
0
2
Order By: Relevance
“…Numerous examples of such models can be found in the literature (e.g., Naab & Ostriker 2006;Romano et al 2006;Worthey et al 2005;Scannapieco et al 2005;Valle et al 2005;Lanfranchi & Matteucci 2004;Oey 2000, among many recent discussions). These have been developed all the way to full hierarchical-merging and chemodynamical-evolution codes (e.g., Kawata & Gibson 2003;Cole et al 2000;Beasley et al 2003;Somerville & Primack 1999).…”
Section: A Chemical Evolution Modelmentioning
confidence: 99%
“…Numerous examples of such models can be found in the literature (e.g., Naab & Ostriker 2006;Romano et al 2006;Worthey et al 2005;Scannapieco et al 2005;Valle et al 2005;Lanfranchi & Matteucci 2004;Oey 2000, among many recent discussions). These have been developed all the way to full hierarchical-merging and chemodynamical-evolution codes (e.g., Kawata & Gibson 2003;Cole et al 2000;Beasley et al 2003;Somerville & Primack 1999).…”
Section: A Chemical Evolution Modelmentioning
confidence: 99%
“…Adopting an average of n ∼ 5 × 10 4 , he suggested that fluctuations would be relatively small. More detailed models for overlapping contaminations were studied by Roy & Kunth (1995), Argast et al (2000) and Oey (2000). Oey (2003) used turbulent dispersal from Bateman & Larson (1993) to enlarge the effective sizes and reduce the average metallicities in the overlapping regions.…”
Section: How Large Should Metallicity Fluctuations Be?mentioning
confidence: 99%
“…This question leads us to another: What are the number and the metallicities of stars enriched by any given number of SNe? Several chemical evolution models have been developed to study the effect of small number statistics on the build-up of chemical elements in the early Galaxy (e.g., Tsujimoto et al 1999;Argast et al 2000;Oey 2000;Travaglio et al 2001). However, these models do not explicitly trace or discuss the metallicity distributions of individual populations of stars enriched by a specific number of SNe.…”
Section: Introductionmentioning
confidence: 99%